Particle emissions of two unblended alternative jet fuels in a full scale jet engine. (15th November 2019) - Schripp, T.; Herrmann, F.; Oßwald, P.; Köhler, M.; Zschocke, A.; Weigelt, D.; Mroch, M.; Werner-Spatz, C.
Highlights: Two unblended alternative jet fuels were tested on a CFM56 jet engine. Particle emission followed the hydrogen content of the fuels. One ASTM non-compliant fuel led to a reduction of 70% in particle emission. Different transient patterns were applied and compared to steady-state processes. Abstract: The emission of soot particles from aircraft jet engines is relevant due to their impact on contrail formation and local air quality in airport areas. The reduction of particle emission may be achieved by changes in jet engine design. This, however, will only affect new aircraft. Previous studies have shown that the use of alternative jet fuels feature a co-beneficial reduction of soot emission beside an improved carbon footprint. In the present study, a CFM56-5C4 engine was operated on a test rig with three different fuel types: one reference kerosene, a catalytic hydrothermolysis jet fuel (ReadiJet) and an unblended alcohol-to-jet (ATJ) fuel. Due to the absence of aromatics in the ATJ fuel, ASTM jet fuel requirements are not met, but the use of this fuel led to a reduction of 70% in particle mass compared to the reference fuel. The ReadiJet fuel has higher aromatic content, lower fuel hydrogen content and, thus, an increase in particle emission was observed. For the present engine, the highest soot reductions were observed at lower power settings. In accordance to previous studies, the soot emission showed a good correlation to the hydrogen content of the fuels and the emission reduction matches the estimations of the imFOX model. In order to compare test rig studies to field studies, transient processes must be considered because they govern take-off conditions. Four experiments with different transient thrust patterns were performed on the test rig with regular Jet A-1. If the thrust changes were not very rapid (e.g. 5 s to 90% thrust) the results could be reproduced with a set of pseudo-stationary processes to a sufficient extend. This emphasizes the relevance of test-rig studies for real in-field measurements and local air quality studies.